Body composition and somatotype profile of male Zimbabwean junior soccer players - Makaza, D.; Amusa, L. O.; Goon, D. T.; Tapera, E. M.; Gundani, M. P. (Medicina dello Sport, 2012)
Aim. The aim of this study was to assess the body composition and somatotype profile of junior Zimbabwean Premier League club junior league football players based in Bulawayo, Zimbabwe.